Pertanggungjawaban Hukum Jasa Pengangkutan Darat Terhadap Kerusakan Barang Penumpang - Joni Saputra (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
The goal of this research is to determine and analyze the forms of liability arrangements if the broken of passengers’ goods happened. The writing of this journal uses the type of normative research where the applicable laws and regulations are studied and uses secondary data as the main data. Based on the research results, the following conclusions can be formulated: (1) Transport organized and carried out by public transport services is used to carry people or goods from one place to another safely, a form of responsibility carried out by public transporters in the event of an accident or damage to goods caused by the common carrier is referring to the initial agreement that has been previously agreed upon by both parties; and (2) The responsibilities that must be carried out and carried out by public transportation companies in the event of damage to passenger goods are contained in the Consumer Protection Law No. 8 of 1999.